2012
DOI: 10.3233/jad-2011-111307
|View full text |Cite
|
Sign up to set email alerts
|

Altered NEP2 Expression and Activity in Mild Cognitive Impairment and Alzheimer's Disease

Abstract: Neprilysin-2 (NEP2), a close homolog of neprilysin (NEP), degrades amyloid-β (Aβ) and serves an important role in clearing Aβ in vivo. We measured NEP2 and NEP mRNA levels from non-impaired (NI), mild cognitive impaired (MCI), and clinical Alzheimer’s disease (AD) subjects in the mid-temporal gyrus, mid-frontal gyrus, caudate, and cerebellum. NEP2 activity levels were also determined. Our results indicate that NEP2 and NEP mRNA expression is altered in MCI subjects relative to NI subjects in AD-susceptible reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 35 publications
(31 reference statements)
0
16
1
2
Order By: Relevance
“…The levels of the Aβ-degrading enzyme neprilysin are reduced in human dementia pugilistica cases. Though MME/neprilysin is high in blood in this and other studies, levels of NEP and NEP2 have been reported to be lower, higher or unchanged in AD brain 17 . Notably, Neprilysin protects against cerebral amyloid angiopathy and Aβ-induced degeneration of cerebrovascular smooth muscle cells 18 .…”
Section: Discussioncontrasting
confidence: 47%
“…The levels of the Aβ-degrading enzyme neprilysin are reduced in human dementia pugilistica cases. Though MME/neprilysin is high in blood in this and other studies, levels of NEP and NEP2 have been reported to be lower, higher or unchanged in AD brain 17 . Notably, Neprilysin protects against cerebral amyloid angiopathy and Aβ-induced degeneration of cerebrovascular smooth muscle cells 18 .…”
Section: Discussioncontrasting
confidence: 47%
“…NEP2 shows a different subcellular localization from NEP (Whyteside & Turner, ) and does appear to have a significant contribution to Aβ metabolism in vivo, at least from transgenic studies in AD mouse models (Marr & Hafez, ). Furthermore, NEP2 activity levels are reduced in mild cognitively impaired individuals and AD patients relative to nonimpaired subjects in AD‐susceptible brain regions (Huang, Hafez, James, Bennett, & Marr, ). NEP2 may even prove to be a more selective therapeutic target for up‐regulation of Aβ clearance than NEP itself since it has a more restricted substrate specificity (Whyteside & Turner, ).…”
Section: The Key Adesmentioning
confidence: 99%
“…мента в теменной и фронтальной коре головного мозга у аналогичных групп пациентов [22]. Согласно полученным данным, основная холинэсте-разная активность крови обусловлена наличием в плазме БХЭ, поскольку уровень общей активности этого фермен-та на 1-2 порядка выше, чем АХЭ (см.…”
Section: результаты и обсуждениеunclassified
“…В ранее опубликованных исследованиях было по-казано, что содержание НЕП и его мРНК у больных БА являются достоверно более низкими, чем у пациентов контрольной группы соответствующего возраста [21]. Данные литературы также свидетельствуют о том, что со-держание мРНК НЕП и активность его гомолога НЕП2 снижается в средневисочной и среднелобной извилинах, хвостатом ядре и мозжечке головного мозга пациентов с синдромом мягкого когнитивного снижения амнестиче-ского типа (а-MКC) и БА [22]. Дефицит активности НЕП в коре и гиппокампе также наблюдается у животных с на-рушенными когнитивными функциями [16,[23][24][25][26][27].…”
unclassified